Spontaneous pneumothorax complicating lung emphysema. So, what's the catch? (Medical Journal of Indonesia, 2013)
Spontaneous pneumothorax secondary to lung carcinoma is very rare (0.05% of all pneumothoraces). We report a case of a 66-year-old male with persistent right-sided spontaneous pneumothorax, initially suspected as secondary to bullous emphysema. Intraoperative findings consisted of an apical bulla with a nonspecific carnification at its base and a bulla at the lower lobe. Surprisingly, histological examination revealed an undefined non-small cell carcinoma. Although spontaneous pneumothorax associated with lung carcinoma is rare, suspicion for malignancy should be raised in patients over 40 presenting with spontaneous pneumothorax, especially in high risk patients such as smokers or patients with chronic bronchitis or emphysema. (Med J Indones. 2013;22:54-6) Keywords: Emphysema, lung cancer, pneumothorax